Risk and protective factors influencing educational success and suicidality for First Nations youth-in-care in Ontario, Canada - Greenberg, Barbara; Miller, Meagan; Michael, Erik; Flynn, Robert J. (2016)
Presented at the XIVth European Scientific Association on Residential and Family Care for Children and Adolescents (EUSARF) international conference in Oviedo, Spain in September, 2016